1997
DOI: 10.1063/1.119990
|View full text |Cite
|
Sign up to set email alerts
|

Formation of diamond in carbon onions under MeV ion irradiation

Abstract: Spherical carbon onions are generated by irradiating graphitic carbon soot with Ne+ ions of 3 MeV energy. Under continued irradiation, a transformation of their cores to cubic diamond crystals is observed. In comparison to earlier electron irradiation experiments, the yield of diamond is much higher. The output of the irradiation experiment is characterized by electron microscopy and electron energy loss spectroscopy. Knock-on displacements of carbon atoms by Ne+ ions are assumed to be responsible for a self-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 5 publications
1
77
0
Order By: Relevance
“…284 Besides this, ordering of fullerene thin films under highenergy ion irradiation ͑200 MeV Au and 60 MeV Ni ions͒ has been reported, 66 probably due to effects of ion-beam heating and a vanishingly small probability for defect production in a very thin target. Besides this, fullerene films irradiated with 250 keV Ar and 92 MeV Si ions showed magnetic response, 285 as evidenced by magnetic measurements using a superconducting quantum interference device and magnetic force microscopy.…”
Section: Ion Irradiation Of Fullerenes and Fullerene-nanotube Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…284 Besides this, ordering of fullerene thin films under highenergy ion irradiation ͑200 MeV Au and 60 MeV Ni ions͒ has been reported, 66 probably due to effects of ion-beam heating and a vanishingly small probability for defect production in a very thin target. Besides this, fullerene films irradiated with 250 keV Ar and 92 MeV Si ions showed magnetic response, 285 as evidenced by magnetic measurements using a superconducting quantum interference device and magnetic force microscopy.…”
Section: Ion Irradiation Of Fullerenes and Fullerene-nanotube Systemsmentioning
confidence: 99%
“…It had been earlier shown that closed-shell carbon nanostructures, such as carbon onions, can act as self-contracting high-pressure cells under electron 6 and ion 284 irradiation, and that high pressure buildup in the onion cores can even induce graphitediamond transformations ͑see Ref. 72 for a review͒.…”
Section: E Irradiated Carbon Nanotubes and Onions As Highpressure Cellsmentioning
confidence: 99%
“…As more atoms are added, sp 3 -rich domains emerge and grow towards the center. There they fuse and form a highly fourfold-coordinated condensate as is indicated in Table I by the large fraction of Figure 3 shows the total number of sp 3 -hybridized atoms in the largest sp 3 -bonded cluster during the addition. The neighboring atoms are considered to belong to a same cluster if they share a sp 3 bond.…”
mentioning
confidence: 99%
“…1 Further electron or heavy ion irradiation causes the fullerenes to transform into diamond near their centers. 2,3 The irradiation process is viewed to induce knockon displacements, collision cascades, and flux of C atoms towards the core, resulting in increase in the particle density, local pressure, and temperature. Finally, the conditions become preferable for the nucleation of diamond.…”
mentioning
confidence: 99%
“…However, no cauliflowertype structures have ever been observed among furnaceproduced carbon black particles, many of which have experienced grain-grain collisions near the speed of sound. It seems more likely that the onions would have produced diamonds at their centers instead, which they do when powerfully irradiated with electrons or ions (Banhart & Ajayan 1996;Banhart et al 1997;Wesolowski et al 1997). …”
Section: Calculations and Resultsmentioning
confidence: 99%